EFISIENSI PEMASARAN RAJUNGAN DI KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR - Nugroho, Rahmadi; Endaryanto, Teguh; Indriani, Yaktiworo (Lampung University, 2025)
This study aims to analyze the marketing efficiency of blue swimming crab in Labuhan Maringgai District, East Lampung Regency. The analytical method used was quantitative descriptive analysis to analyze marketing channels, marketing margins and marketing efficiency. This research was conducted in Muara Gading Mas Village and Margasari Village, Labuhan Maringgai District, East Lampung Regency. The number of respondents was 60 people including fishermen, breeders, miniplant owners in Labuhan Maringgai District, and UPI in Lampung Province. Data collection was carried out from November to December 2023. The results of the research show that the marketing channel for blue swimming crab in Labuhan Maringgai District has two marketing channels, namely marketing channel I (fishermen-miniplant-UPI), and marketing channel II (fisherman-middleman-miniplant-UPI). Marketing margin for blue swimming crabs in Labuhan Maringgai District, supervisory marketers have a marketing margin of IDR 19.941/kg. Miniplant marketing margin in marketing channel I is IDR 130.551/kg and Marketing Channel II is IDR 132.047/kg. UPI's marketing margin on marketing channels I and II is IDR 184,000/kg. The marketing efficiency of blue swimming crab in Labuhan Maringgai District in each marketing channel categorizes as inefficient because the value is more than 5% (Eps > 5%), except for middleman. Keywords: blue swimming crab, efficiency, fisherman, marketing